2016
DOI: 10.15252/emmm.201506039
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR /Cas9‐mediated somatic correction of a novel coagulator factor IX gene mutation ameliorates hemophilia in mouse

Abstract: The X‐linked genetic bleeding disorder caused by deficiency of coagulator factor IX, hemophilia B, is a disease ideally suited for gene therapy with genome editing technology. Here, we identify a family with hemophilia B carrying a novel mutation, Y371D, in the human F9 gene. The CRISPR/Cas9 system was used to generate distinct genetically modified mouse models and confirmed that the novel Y371D mutation resulted in a more severe hemophilia B phenotype than the previously identified Y371S mutation. To develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 39 publications
1
115
1
2
Order By: Relevance
“…In delivering CRISPR‐Cas9 to mouse mammary glands with lentiviruses, one study reported immune cell infiltration that cannot be suppressed by immunosuppression . Another study compared naked DNA hydrodynamic transduction and adenoviral delivery of CRISPR‐Cas9 into hemophilic mice for correcting a transgenic human factor IX mutation . Hydrodynamic plasmid delivery resulted in 0.5–1.5% gene correction that was sufficient to confer the desired blood clotting ability.…”
Section: Preclinical Evidence Of Immunity Against Crispr Systemsmentioning
confidence: 99%
“…In delivering CRISPR‐Cas9 to mouse mammary glands with lentiviruses, one study reported immune cell infiltration that cannot be suppressed by immunosuppression . Another study compared naked DNA hydrodynamic transduction and adenoviral delivery of CRISPR‐Cas9 into hemophilic mice for correcting a transgenic human factor IX mutation . Hydrodynamic plasmid delivery resulted in 0.5–1.5% gene correction that was sufficient to confer the desired blood clotting ability.…”
Section: Preclinical Evidence Of Immunity Against Crispr Systemsmentioning
confidence: 99%
“…Despite its growing popularity, however, the CRISPR/Cas9 system is not perfect, as the guide RNA can bind to similar sites outside of the targeted gene, potentially leading to unspecified and unintended mutations, thus limiting both its research value and clinical potential (Fu et al, 2013). Nevertheless, CRISPR/Cas9 has been used to correct defects in several genes, including genes linked to Duchenne muscular dystrophy, metabolic liver disease, and hemophilia B (Guan et al, 2016; Long et al, 2016; Maggio et al, 2016; Nelson et al, 2016; Tabebordbar et al, 2016). Correcting a point mutation requires that the Cas9 protein, guide RNA, and donor template for recombination are introduced together into the same cells.…”
Section: Retinal Gene Therapy and Crispr/cas9mentioning
confidence: 99%
“…Compared with ZFN and transcription activator-like effector nuclease (TALEN), the CRISPR/Cas9 system can edit multiple genes simultaneously and has few species limitations Ceasar et al, 2016). At present, CRISPR/Cas9 technology has been widely used in animal modeling Lu et al, 2017), disease research (Maresch et al, 2016), gene therapy (Guan et al, 2016;Wei et al, 2016), and other fields.…”
Section: Introductionmentioning
confidence: 99%